Implementation of knowledge-based engineering methodology in hydraulic generator design. (6th May 2015) - Guo, Wei; Wen, Jiafu; Shao, Hongyu; Wang, Lei
Hydraulic generator design companies are always being exhorted to become more competitive by reducing the lead time and costs for their products for survival. Knowledge-based engineering technology is a rapidly developing technology with competitive advantage for design application to reduce time and cost in product development. This article addresses the structure of the hydraulic generator design system based on the knowledge-based engineering technology in detail. The system operates by creating a unified knowledge base to store the scattered knowledge among the whole life of the design process, which was contained in the expert's brain and technical literature. It helps designers to make appropriate decisions by supplying necessary information at the right time through query and inference engine to represent the knowledge within the knowledge-based engineering application framework. It also integrates the analysis tools into one platform to help achieve global optimum solutions. Finally, an example of turbine-type selection was given to illustrate the operation process and prove its validity.